ANALISIS : KESULITAN SISWA DALAM MEMAHAMI SISTEM ORGAN MANUSIA DAN IMPLIKASINYA TERHADAP PEMBELAJARAN IPA - Afifah, Afifah Dwi Ramadhani; Rian Vebrianto; Nurhasanah; Mery Borilian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is a fundamental process in the development of individuals and society. Through education, knowledge, skills, values, and attitudes are transferred from one generation to the next, enabling intellectual, social, and emotional development. The purpose of this study was to determine the problems related to materials that are considered difficult and how to solve these learning problems in science learning in elementary schools. This research method uses a mix-method research type where quantitative data is reinforced with qualitative data. This study involved two science teachers and 25 fourth-grade elementary school students. The instruments used included questionnaires, interview sheets, and observation sheets. Data were collected by going directly to the field and analyzed using descriptive analysis for quantitative data and analysis of interview results for qualitative data. The results showed that there were two materials that were considered difficult by fourth-grade elementary school students, namely the Human Organ System (40%) and Photosynthesis (36%). The solutions used for the Human Organ System material usually use learning video media and e-learning platforms as supporting media. Meanwhile, for the Photosynthesis material, the solution provided was the use of practical demonstration tools and a digital microscope. The conclusion of this study is that video learning media, e-learning platforms, practical demonstration tools, and digital microscopes can be alternative solutions in helping students understand material that is considered difficult.